English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3s^2+8s+4

2006-12-06 12:35:39 · 5 answers · asked by Kendall 1 in Science & Mathematics Mathematics

5 answers

use Puggy methode...

2006-12-06 13:25:17 · answer #1 · answered by eL'do-radO 3 · 0 1

By trial and error. You at least know that you're going to have 3s and s in the brackets.

(3s + ?) (s + ?)

Your goal is to find out what those question marks are. What you have to do is test two numbers that multiply to make 4 (since 4 is the third term). Then you have to test the OUTER and INNER (of FOIL) to determine if they add up to make the middle term, 8s.

Let's try 1 and 4

(3s + 1) (s + 4)

The OUTER is equal to 4(3s), and the INNER is equal to 1(s), or 12s and s respectively, and they DON'T add up to the middle term, 8s (they add up to 13s). So you have to try again.

Let's try 4 and 1.

(3s + 4) (s + 1)
OUTER = 1(3s) = 3s
INNER = 4(s) = 4s
Added together, they give 7s, which is NOT the middle term.

Let's try 2 and 2.

(3s + 2) (s + 2)

OUTER = 2(3s) = 6s
INNER = 2(s) = 2s

6s + 2s = 8s, so this is the correct factorization!

(3s+2)(s + 2)

2006-12-06 20:42:57 · answer #2 · answered by Puggy 7 · 1 0

I'd factor it this way

3s^2+8s+4=(3s+2)(s+2)

2006-12-06 21:09:12 · answer #3 · answered by dennismeng90 6 · 1 0

3s^2+8s+4 =0 is a quadratic equation
8s can be factorized as 2s and 6s as it adds up to 8 and multiplies to form 12
so..3s^2+6s+2s+4=0
(3s^2 + 6s)+(2s+4)=0
3s (s+2)+ 2(s+2)=0
(3s+2)=0: (s+2)=0
s= -2/3 : s= -2

2006-12-06 20:58:00 · answer #4 · answered by Smj 1 · 0 1

You can factor it as long as you tell what is the variable such as:

s = 4

3s^2+8s+4=

12^2+32+4=

6+32+4=42

2006-12-06 20:39:43 · answer #5 · answered by Friendly Fire 2 · 0 1

fedest.com, questions and answers